Chronic kidney disease and acute kidney injury in arthroplasty patients over 65 years of age. Issue 7 (19th March 2019) - Nikkinen, Okke; Nieminen, Teemu; Alahuhta, Seppo; Ohtonen, Pasi; Vakkala, Merja
Abstract : Background: The purpose of this study was to evaluate the prevalence of chronic kidney disease (CKD) and the incidence of perioperative acute kidney injury (AKI) in primary arthroplasty patients over 65 years of age. Risk factors, perioperative events and the outcome of surgery were evaluated. Methods: This retrospective, hospital register‐based study consists of patients operated in 2014 in the area of Oulu, Finland. The estimated glomerular filtration rate (eGFR) was calculated using the Chronic Kidney Disease Epidemiology Collaboration formula. The incidence of AKI was evaluated based on the serum creatinine criteria of the KDIGO (Kidney Disease, Improving Global Outcomes) classification. Results: Of the 807 patients, 60.8% had mildly decreased (60‐89 ml/min/1.73 m 2 ) and 13.5% moderately to severely decreased eGFR (<60 ml/min/1.73 m 2 ) preoperatively. Only 33.9% of patients with an eGFR < 60 ml/min/1.73 m 2 had a diagnosis of a kidney disease. In emergencies, 46.9% of patients with an eGFR < 60 ml/min/1.73 m 2 were deceased at the 12‐month follow‐up point. The measurement of postoperative sCr was not complete (477/807) and was allocated to emergencies and older patient with more comorbidities. Of those whose postoperative sCr was available, 14 (2.9%) fulfilled AKI criteria. Most of the AKI cases had a decrease in eGFR preoperatively, a diagnosed kidney disease or diabetes mellitus. Conclusions: Impairment of kidney function was common and was related to mortality in emergency arthroplasties. Measurements of postoperative sCr were allocated to high risk patients. Preoperative kidney function, kidney disease and diabetes mellitus were important determinants for perioperative AKI.